Planning of Sewage Sludge Treatment Plant Poso Regency - Ahmad Syaeful Huda; Maritha Nilam Kusuma (Journal of Civil Engineering, Planning and Design, 2022)
In order to process the fecal sludge that is collected from the residents of Poso Regency, a Sewage Sludge Treatment Plant has been built. For the purpose of treating sewage sludge, this facility is one method utilized to enhance wastewater quality. There is a Sewage Sludge Treatment Plant in Poso Regency, however, it is in disrepair and cannot meet current needs. In light of this, Poso Regency needs cutting-edge technology for treating sewage sludge. The goal of this research was to establish the average entry of fecal sludge and its volume for Poso Regency to create an appropriate system that meets all requirements set forth by the Ministry of Public Works.